Metacognitive skills development in young soccer athletes of different playing positions - da Silva, V. F.; Silva, E. V.; Oliviera, F. A. (2001)
This study examined if a long-term metacognitive soccer program would differently influence the development of soccer related abilities in learners of different field playing position. The metacognive items for evaluation were anticipatory strategies, decision making, mental imagery, coding and rehearsal. These items were practiced in kinesthetic, visual, and "mental" modalities. Subjects were 60 naive soccer practitioners between 9 and 10 year-of-age, males. They formed 3 groups named mid-field (MSL), defensive (DSL), and offensive (OSL) soccer learners. Each group included 20 individuals divided into two subgroups. One of those represented the group respective control. Prior to the program, a baseline test of soccer metacognitive proficiency (Adapted from Johnson, 1991) was given for all participants. The same abilities named processing strategies, response time, object timing, and use of tactical skills were again tested after the program conclusion. An ANOVA 6 (groups) X 3 (processing strategy) X (reaction time modalities) X 3 (object timing modalities) revealed significant interaction between Groups X strategy (p< 0.05), Groups X Reaction time Modalities (p < 0.001), and Groups X Object timing modalities (p < 0.001). Tuckey test indicated that as related to each group pair, the individuals practicing the metacognitive soccer-training program were better than their respective control pairs. Also that the effects of the program were different when analyzed in relation to playing position. That is, mid-field players benefited more than offensive and defensive players, and offensive, more than the defensive ones. Same effects were observed in qualitative observations in a real game situation.